503. TOTAL ESOPHAGECTOMY AND GASTRIC PULL UP FOR POST CORROSIVE ESOPHAGEAL STRICTURE: FEASIBLE IN MOST CASES WITH EXCELLENT OUTCOME. (24th September 2022) - Ezz, Reda; Sabry, Karim
Abstract: Post corrosive esophageal stricture represent a big national problem in Egypt because of bad culture of using (POTASH K2CO3) a highly corrosive substance for washing clothes with accidental (children) or sometimes suicidal (adult) swallow of this corrosive substance. Extensive esophageal stricture resulted is the late consequence of such swallow with complete or partial dysphagia leading to severe malnutrition and death of many patients. Dilation was successful in mild cases and many other cases required surgery. We present our new surgical strategy in managing 96 cases of post corrosive esophageal stricture including early feeding jejunostomy as well introduction of MI technique. From January 2016 to January 2022, 96 cases of failed dilation post corrosive esophageal stricture were included in the study. Three- fields total esophagectomy and gastric pull up with cervical stapled esophago-gastric anastomosis was the operation used for all cases. Pyloroplasty and feeding jejunostomy were done for all cases We followed the cases for development of any complications (leak, bleeding, respiratory problems and stricture). Laparoscopy was used in 49 (51%) cases and was successfully completed in 42cases (86%). Right thoracotomy and left cervicotomy were used in all cases. Mean operative time was 368 minutes. Early complications were in the form of leak: cervical 12 cases (12.5%), from pyloroplasty 3 cases (3%). All cases managed conservatively. Only one pyloroplasty leak required exploration. Bleeding occurred in 5 cases (5%) and managed conservatively. Respiratory problems occurred in 37 cases (39%) requiring prolonged intubation in 3 cases (3%). Postoperative dysphagia was noted in 9 cases (9%) due to anastomotic stricture managed by dilation. No mortality recorded. Our short- and long-term results of total esophagectomy and gastric pull up for post corrosive esophageal stricture are excellent with low morbidity and no mortality.